Application of compost in the different of pen culture substrates type for the intensification of sea cucumber, Holothuria scabra (Jaeger 1883) culture. Issue 1 (1st June 2022) - Sabilu, K; Supriyono, E; Nirmala, K; Subhan; Ketjulan, R; Hamzah, M; Rahman, A; Patadjai, R S; Alwi, L O; Sabilu, M
Abstract: Intensification of aquaculture is directed at the effort to increase productivity by carrying capacity of production factors. This study was conducted to evaluate the growth performance of Holothuria scabra cultured intensively through the application of compost fertilizer. H. scabra were reared for 90 days (20 individuals/m 2 of density), using a pen culture method on the three different substrates, namely fine sand, seagrass mud, and coarse sand, where each treatment was made as four replicates. The amount of compost used for the type of each substrate was the same. The results showed that applying compost in sea cucumbers culture using the pen culture method was proven to be effective in increasing the growth performance of sea cucumbers H. scabra, with the weight gain, growth rate, and survival, respectively, ie: 49.10±1.62 g; 1.26±0.03% g/day and 90.00% on seagrass mud substrate; 46.00±6.92 g; 1.23±0.11% g/day and 89.00% on a fine sand substrate and the lowest is 42.05±g; 1.13±0.08% g/day and 87.50% were found on a coarse sand substrate. The growth response was not significantly different between the three substrate types (Duncan's test, p>0.05), indicating that the availability of nutrient sources in substrates is one of the key factors for the intensification of H. scabra culture.